New Perspective on Writing History during the Glory of the Islamic Empire in the Archipelago - Ilyas, Yusran; Padiatra, Aditia Muara (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2024)
This journal discusses a new perspective on history in the XV-XVII centuries in the archipelago. This new perspective tries to balance the orientalist perspective and perfect the local perspective in depicting history during the Islamic kingdoms in the archipelago. This new perspective at least reduces the historical narrative that explains the superiority of